Algonquian materials, Frank G. Speck Papers - Speck, Frank G. (Frank Gouldsmith), 1881-1950; Skinner, Alanson, 1886-1925; Butler, Eva L.; Sapir, Edward, 1884-1939; Voegelin, C. F. (Charles Frederick), 1906-1986 (1918)
A variety of materials relating to Speck's study of diverse Algonquian peoples, cultures, and languages. Includes his "Remnants of the Eastern Indian Tribes," a brief discussion of location of New England Algonquians; his favorable review of John M. Cooper, "Snares, Deadfalls, and other Traps of Northern Algonquians and Northern Athapascans" [Printed, Speck (1939).]; a "Table of Double Curve Motif," charting techniques and variations of motifs of various Northwestern, Iroquoian, and central Algonquian peoples; a manuscript draft and additions of "Terms of relationship and the family territorial band among the Northeastern Algonquins," [Printed, Speck (1918).]; letters from Alanson Skinner challenging Speck's ethnic position of the Southeastern Algonquian on meaning of Eskimo-type artifacts found in Algonquian site in New York (State); materials from Eva L. Butler, including two pamphlets containing transcriptions of historical letters, principally from the Connecticut State Library--"Colonial Letters of our Ancestors" and "Letters of the Indians"--and "Botany and ethnozoology of the New England Indians," a bibliography of seventeenth- and eighteenth-century sources for ethnobotantical and ethnozoological references; letters from Edward Sapir concerning Speck (1918a), particularly Yurok comparisons, his excitement about reduction of language stocks, and possible typographical errors; and letters from Carl F. Voegelen concerning the usefulness of Speck's Naskapi material for comparative study of Algonquian languages and seeking an article on process by which Algonquian languages become extinct.